Synthesis and electrical properties of Pb(Mg1/3Nb2/3)O3-PbTiO3ceramics - R. Wongmaneerung (2018)
Ceramic compositions of a combination between lead magnesium niobate, Pb(Mg1/3Nb2/3)O3, and lead titanate, PbTiO3, were fabricated by using Mg4Nb2O9precursor technique. Their electrical properties with respect to temperature and frequency were examined and the effect of sintering conditions on phase formation, densification, microstructure and electrical properties of the ceramics were examined. It has been found that optimisation of sintering condition can lead to a highly dense and pyrochlore-free PMN-PT ceramics. The gradual decreasing of the physical properties of the sintered ceramics was related to the gradual decrease of density and inhomogeneous microstructure. The results also revealed that for the lower concentration of lead titanate a relaxor behavior is noticed with a high electrostrictive effect, which was almost hysteretic free. However, higher amount of lead titanate led to a normal ferroelectric behavior. © 2008 Elsevier B.V. All rights reserved.